PENERAPAN MODEL PENDIDIKAN GERAK UNTUK MENINGKATKAN KETERAMPILAN SISWA SD BERMAIN LOMPAT TALI BASIC DOUBLE DUTCH - Alif Fauji Dermawan, - (2019)
The research was motivated by the lack of skills to play jumping rope students SDN 032 Tilil. The research was intended or demonstrated to implement a motion education model to increase the playing activity of basic double Dutch rope jumping. The methods used in this research were class action research with Instruments, Australian Rope Skipping Association, and Field records. The participants of this research were 32 students of V C SDN 032 Tilil. In the academic year 2019/2020, consisted of (19 men and 13 women). Results of pre-test showed from play basic double dutch is reached 51.72%; In 1 Cycle action 1 reaches 54.69%; At Cycle 1 The action 2 reaches, 56.41%; In Cycle 2 Action 1 reaches 70.00%; And in Cycles 2 action 2 reaches, 77.50%. Thus it can be concluded that the implementation of the model of motion education can increase the playing activity of basic double Dutch rope jumping on students V C class of SDN 032 Tilil